Underestimation of pancreatic cancer in the national cancer registry – Reconsidering the incidence and survival rates. (February 2017) - Fest, J.; Ruiter, R.; van Rooij, F.J.A.; van der Geest, L.G.M.; Lemmens, V.E.P.P.; Ikram, M.A.; Coebergh, J.W.; Stricker, B.H.; van Eijck, C.H.J.
Abstract: Background: In the Netherlands, like in many other European countries, pancreatic cancer mortality was found to be systematically higher than the incidence. This suggests that there is an underestimation of the reported incidence of pancreatic cancer. Aim: We aimed to study the incidence of pancreatic cancer in the Rotterdam area and to compare this with the national level. Methods: This study is embedded in the Rotterdam Study (RS), an ongoing population-based prospective cohort study of people aged 45 years and above, enrolled between 1989 till 2006. Details on incident pancreatic cancer cases were available until 2013. Age-specific incidence rates were calculated and compared with data available in the Netherlands Cancer Registry. Results: At baseline 14, 922 participants were at risk of developing pancreatic cancer. Median follow-up time was 16.4 person years per person. In total, 113 participants developed pancreatic cancer. Rates increased with age with an incidence rate of 109.9 (95% confidence interval [CI]; 85.7–138.8) per 100, 000 person years for people older than 75. This is higher than the currently reported 55.9–89.2 per 100, 000 person year. Of the 113 cases identified in the RS, only 67.3% was reported as pancreatic cancer in the Netherlands Cancer Registry. Cases that were not registered were significantly older and had significantly poorer survival. Conclusion: The incidence of pancreatic cancer, as registered by the Netherlands Cancer Registry, is an underestimation. Patients, not registered by the cancer registry, have a significantly poorer survival. Consequently, we probably overestimate the already poor survival of pancreatic cancer. Highlights: The national cancer registry underestimates the incidence rate of pancreatic cancer. More than 30% of the pancreatic cancer cases are missed by the national cancer registry. Pancreatic cancer cases that are missed by the registry have a poorer survival. We probably overestimate the already poor survival of pancreatic cancer.